Susceptibility to Insecticides and Natural Infection in Aedes aegypti: An Initiative to Improve the Mosquito Control Actions in Boyacá, Colombia - Omar Cantillo-Barraza (Ubiquity Press, 2020)
Background: Integrated management strategies for dengue prevention and control have been the main way to decrease the transmission of arboviruses transmitted by 'A. aegypti' in Colombia. However, the increase of chikungunya (CHIKV), Zika, and dengue (DENV) fever cases suggests deficiencies in vector control strategies in some regions from this country. Objective: This work aimed to establish a baseline susceptibility profile of 'A. aegypti' to insecticides, determine the presence of 'kdr' mutations associated with resistance to pyrethroids, and detect natural arbovirus infection in this vector from Moniquirá – Boyacá, one of the most endemic cities in Colombia. Methods: Mosquitos were collected in six neighborhoods, and colonies established in the laboratory. Susceptibility to malathion and lambda-cyhalothrin insecticides was evaluated, and we examined the point mutations present in portions of domains I, II, III, and IV of the sodium channel gene using a simple allele-specific PCR-based assay (AS-PCR). Findings: 'A. aegypti' from Moniquirá showed decreased susceptibility to pyrethroid insecticides, and kdr mutations 419L, 1016I, and 1558C with allelic frequencies of 0.39, 0.40 and 0.95, respectively, were observed. The minimal infection rate (MIR) to DENV-1 was 44.1, while to CHIKV was 14.7. Conclusions: We establish a baseline insecticide resistance, 'kdr' mutations, and arbovirus circulation, which contain the elements necessary for the consolidation of a local surveillance strategy with an early warning system and rational selection and rotation of insecticides.